Elementary Geometry for College Students (6th Edition)

Published by Brooks Cole
ISBN 10:
ISBN 13:

Appendix A - A.1 - Algebraic Expressions - Exercises - Page 534: 13c

Answer

$= 18$

Work Step by Step

$= (-12) \div (-\frac{2}{3})$ $= (-12) \times \frac{3}{-2}$ $= \frac{-36}{-2}$ $= \frac{36}{2}$ $= 18$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.